2012
DOI: 10.1002/art.34424
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β‐catenin signaling is hyperactivated in systemic sclerosis and induces Smad‐dependent fibrotic responses in mesenchymal cells

Abstract: Introduction Fibrosis in human diseases and animal models is associated with aberrant Wnt/β-catenin pathway activation. The regulation, activity, mechanism of action and significance of Wnt/β-catenin signaling in the context of systemic sclerosis (SSc) has not been characterized. Methods Expression of Wnt signaling pathway components in SSc skin biopsies was analyzed. The regulation of profibrotic responses by canonical Wnt/ß-catenin was examined in explanted human mesenchymal cells. Fibrotic responses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
172
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 205 publications
(187 citation statements)
references
References 52 publications
(64 reference statements)
15
172
0
Order By: Relevance
“…For example, b-catenin signaling can upregulate TGF-b message in some but not all contexts (46,47), and TGF-b signaling can lead to b-catenin signaling through Wnt-dependent (10) and-independent mechanisms (48). In our study, alveolar epithelial type 2 cells and leukocytes isolated from Lrp5 2/2 mice manifest reduced capacity to produce TGF-b protein compared with cells isolated from Lrp5 1/1 mice.…”
Section: Discussionmentioning
confidence: 53%
“…For example, b-catenin signaling can upregulate TGF-b message in some but not all contexts (46,47), and TGF-b signaling can lead to b-catenin signaling through Wnt-dependent (10) and-independent mechanisms (48). In our study, alveolar epithelial type 2 cells and leukocytes isolated from Lrp5 2/2 mice manifest reduced capacity to produce TGF-b protein compared with cells isolated from Lrp5 1/1 mice.…”
Section: Discussionmentioning
confidence: 53%
“…Upon activation, fibroblasts differentiate into myofibroblasts, which have a substantially increased potential for the synthesis of ECM, resulting in aggravated fibrosis. Wei and colleagues (38) found that Wnt-3a-induced ␤-catenin activation could stimulate the proliferation and migration of fibroblasts, collagen gel contraction and myofibroblast differentiation, and enhance profibrogenic gene expression. In the present study, we demonstrated that XAV939 could inhibit myofibroblast differentiation and ECM accumulation in vitro and it can also suppress the proliferation of NIH/3T3 fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that canonical Wnt signaling and TGF-β signaling might be mutually reinforcing each other to persistently drive myofibroblast activation in SSc. 30 …”
Section: Tgf-β Regulates Canonical Wnt Signaling On the Level Of Its mentioning
confidence: 99%